SOSIALISASI IMUNISASI DASAR PADA IBU YANG MEMILIKI BALITA DI DESA RIDAN PERMAI TAHUN 2022 - Putri Eka Sudiarti; Zurrahmi Z.R (Universitas Pahlawan Tuanku Tambusai, 2022)
Immunization in the national health system is a very effective form of health intervention in efforts to reduce infant and toddler mortality. Ridan Permai Village is one of the villages in the working area of ??the Bangkinang Public Health Center, Kampar Regency. When a survey was conducted by the team for the head of Ridan Permai Village, information was obtained that there were still several mothers who had not provided basic foundations for their children under five. Toddler age is an age that is vulnerable to various diseases, so this age really needs protection such as providing basic nutrition. Based on the situation analysis and problem assistance mentioned above, a problem can be formulated, namely the need to socialize basic emotions for mothers who have toddlers in Ridan Permai Village. The implementation method used in this activity is in the form of counseling on basic emotions for mothers who have toddlers. This activity took place in Ridan Permai Village on August 12, 2022. The result of this community service is that it can increase the knowledge and desires of mothers who have children under five. It is also hoped that this activity will not end in service activities, but can form cooperation in disseminating information about immunization in improving health status, especially in children under five. Keywords: Basic immunization, Toddlers